Unsmoothing the Cyborg: Technology and the Body in Integrated Dance - Quinlan, Margaret M.; Bates, Benjamin R. (Disability Studies Quarterly, 2014)
Contemporary cyborg theory tends to approach the integration of human bodies and technology innovations as if the cyborg were a unified whole. And, because of the potential of the cyborg body to help ameliorate disability, the cyborg has been suggested as a way to restore function to individuals living with disabilities. We investigate the deployment of the cyborg integrated dance company using theoretical concepts provided by Gilles Deleuze. Rather than observing a smoothly integrated whole, our ethnographic research reveals tensions within the cyborg body. Our analysis revealed three types of creative/reactive forces. Each of these forces comes from the effects/functions of the three striations of the cyborg body: (1) the effects/functions from the machine stria; (2) those from the human stria; and (3) those from the animal stria. Although together these striae constitute the assemblage of the cyborg, as each one takes on greater intensity such that the others are of decreased intensity, the hybridized whole of the cyborg becomes less functional as one is becoming-machine, becoming-human, or becoming-animal.